IMPLEMENTASI PERATURAN DAERAH KABUPATEN KAPUAS HULU NOMOR 13 TAHUN 2018 TENTANG PENGAKUAN DAN PERLINDUNGAN MASYARAKAT HUKUM ADAT DAYAK IBAN SUNGAI UTIK DI DESA BATU LINTANG - JEMI, JEMI; Maryuni, Sri; Erdi, Erdi (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
This study aimed to discover the implementation process of Regional Regulation on the recognition and the indigineous law community protection in Sungai Utik, Batu Lintang Village, Embaloh Hulu Subdistrict, Kapuas Hulu Regency. This study used Charles O. Jones’s Theory which consisted of Organization, Interpretation, and Application. This research used descriptive study with a qualitative approach. The results showed that the organization arrangement in implementing the regional regulation on the recognition and the indigineous law community protection in Sungai Utik was not optimal yet, the  preparation of  recognition and the indigineous law community protection program had been implemented well, and the community’s commitment in implementing the traditional pillars  and maintaining the traditional values of the Iban in Sungai Utik was already optimal with the Decree of Kapuas Hulu Regent Number 561 of 2019 on the recognition of the Sungai Utik indigenous law. This research used descriptive study with a qualitative approach. There was a program to support the implementation of Regional Regulation on the recognition and the indigineous law community protection in Sungai Utik, namely the participatory mapping of the Iban Menua Sungai Utik area and also the identification and verification of the Iban Menua Sungai Utik indigenous law area. The researcher suggests that in the first aspect of organization arrangement, the Batu Lintang Village Government is expected to renew the village’s data and profile t, to make it easier to get valid information about the village and the indigenous territories. Keywords: Implementation, Indigineous Law Community Protection